Combined strategies with PARP inhibitors for the treatment of BRCA wide type cancer - Xie, Yijun; Xiao, Di; Li, Duo; Peng, Mei; Peng, Wei; Duan, Huaxin; Yang, Xiaoping (Frontiers in Oncology, 2024)
Genomic instability stands out as a pivotal hallmark of cancer, and PARP inhibitors (PARPi) emerging as a groundbreaking class of targeted therapy drugs meticulously crafted to inhibit the repair of DNA single-strand breaks(SSB) in tumor cells. Currently, PARPi have been approved for the treatment of ovarian cancer, pancreatic cancer, breast cancer, and prostate cancer characterized by homologous recombination(HR) repair deficiencies due to mutations in BRCA1/2 or other DNA repair associated genes and acquiring the designation of breakthrough therapy. Nonetheless, PARPi exhibit limited efficacy in the majority of HR-proficient BRCA1/2 wild-type cancers. At present, the synergistic approach of combining PARPi with agents that induce HR defects, or with chemotherapy and radiotherapy to induce substantial DNA damage, significantly enhances the efficacy of PARPi in BRCA wild-type or HR-proficient patients, supporting extension the use of PARPi in HR proficient patients. Therefore, we have summarized the effects and mechanisms of the combined use of drugs with PARPi, including the combination of PARPi with HR defect-inducing drugs such as ATRi, CHKi, HR indirectly inducing drugs like VEGFRi, CDKi, immune checkpoint inhibitors and drugs instigating DNA damage such as chemotherapy or radiotherapy. In addition, this review discusses several ongoing clinical trials aimed at analyzing the clinical application potential of these combined treatment strategies.